2003
DOI: 10.1016/s1525-0016(03)00074-1
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of gene transfer and expression in skeletal muscle using enhanced EIAV lentivirus vectors

Abstract: Skeletal muscle is an attractive target tissue for gene therapy involving both muscle and nonmuscle disorders. HIV-1-based vectors transduce mature skeletal muscle; however, the use of these vectors for human gene therapy may be limited by biosafety concerns. In this study, we investigated gene transfer using lentivirus vectors based on the equine infectious anemia virus (EIAV) in skeletal muscle in vitro and in vivo. EIAV vectors transduce proliferating and differentiating C2C12 mouse muscle cells; furthermor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 31 publications
0
29
0
Order By: Relevance
“…Incorporation of the constitutive transport elements CTE and DR-1 resulted in slightly lower gene expression than the parental EIAV vector, similar to our observation of these vectors in mouse skeletal muscle. 16 However, in T-cell lines and in the myeloid cell line MPD, addition of the CTE or DR-1 induced a significant increase in the number of EGFP positive cells. These data suggest that CTE and DR-1 increased the efficiency of transgene RNA processing/ export leading to detectable gene expression in these cell types.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Incorporation of the constitutive transport elements CTE and DR-1 resulted in slightly lower gene expression than the parental EIAV vector, similar to our observation of these vectors in mouse skeletal muscle. 16 However, in T-cell lines and in the myeloid cell line MPD, addition of the CTE or DR-1 induced a significant increase in the number of EGFP positive cells. These data suggest that CTE and DR-1 increased the efficiency of transgene RNA processing/ export leading to detectable gene expression in these cell types.…”
Section: Discussionmentioning
confidence: 97%
“…15 EIAV lentivirus vectors have been investigated in a variety of cell and tissue types including rodent skeletal muscle and central nervous system, fetal mice, and a variety of growing and growth arrested cell lines. [16][17][18][19] We recently demonstrated similar gene transfer into human cell lines between EIAV and HIV-1 vectors, suggesting that EIAV vectors may be clinically relevant for human gene transfer. 19 In this report, we demonstrate that EIAV vectors, unlike FIV vectors, transduce a variety of human hematopoietic cell lines and primary human hematopoietic cells.…”
Section: Introductionmentioning
confidence: 95%
“…For these reasons, but also on account of the accessibility of the endothelium and feasibility of storage of excised donor corneas ex vivo for extended periods, corneal endothelium is an appealing target for gene-based approaches to immunomodulation and protection [35][36][37]. In these studies we used the lentivirus EIAV as the vector for gene transfer, on account of longer term transgene expression and minimal immunogenicity seen with this vector [38,39]. It has been previously demonstrated that a lentivirus containing a reporter gene transduces corneal endothelial cells efficiently, and expression is persistent in corneal cultures maintained up to 60 days.…”
Section: Discussionmentioning
confidence: 99%
“…These data are in agreement with recently published literature. O'Rourke et al 16 reported maintenance of EGFP expression over 3 months after i.m. injection of VSV-G pseudotyped EIAV to adult mice.…”
Section: Gene Transfer To Respiratory Musculature In Uteromentioning
confidence: 99%
“…injection of VSV-G pseudotyped HIV vectors to fetal and adult mice and rats. 10,12,13,16 A lentiviral vector was chosen for this study because of its ability to integrate into target cells, allowing for the possibility of lifetime correction with a single administration of vector. Vector spread after i.v.…”
Section: Gene Transfer To Respiratory Musculature In Uteromentioning
confidence: 99%